Late-Onset Cognitive Impairments after Early-Life Stress Are Shaped by Inherited Differences in Stress Reactivity - McIlwrick, Silja; Pohl, Tobias; Chen, Alon; Touma, Chadi (Frontiers in Cellular Neuroscience, 2017)
Early-life stress (ELS) has been associated with lasting cognitive impairments and with an increased risk for affective disorders. A dysregulation of the hypothalamus-pituitary-adrenal (HPA) axis, the body’s main stress response system, is critically involved in mediating these long-term consequences of adverse early-life experience. It remains unclear to what extent an inherited predisposition for HPA axis sensitivity or resilience influences the relationship between ELS and cognitive impairments, and which neuroendocrine and molecular mechanisms may be involved. To investigate this, we exposed animals of the stress reactivity mouse model, consisting of three independent lines selectively bred for high (HR), intermediate (IR), or low (LR) HPA axis reactivity to a stressor, to ELS and assessed their cognitive performance, neuroendocrine function and hippocampal gene expression in early and in late adulthood. Our results show that HR animals that were exposed to ELS exhibited an HPA axis hyper-reactivity in early and late adulthood, associated with cognitive impairments in hippocampus-dependent tasks, as well as molecular changes in transcript levels involved in the regulation of HPA axis activity (Crh) and in neurotrophic action (Bdnf). In contrast, LR animals showed intact cognitive function across adulthood, with no change in stress reactivity. Intriguingly, LR animals that were exposed to ELS even showed significant signs of enhanced cognitive performance in late adulthood, which may be related to late-onset changes observed in the expression of Crh and Crhr1 in the dorsal hippocampus of these animals. Collectively, our findings demonstrate that the lasting consequences of ELS at the level of cognition differ as a function of inherited predispositions and suggest that an innate tendency for low stress reactivity may be protective against late-onset cognitive impairments after ELS.